3D urban data to assess local urban regulation influence. (March 2018) - Brasebin, Mickaël; Perret, Julien; Mustière, Sébastien; Weber, Christiane
Abstract: Systematically assessing the influence of new urban plans is an important challenge for designing them efficiently. In this paper, we propose a method to assess the influence of local 'Right to Build' regulations on constructibility. Our method is based on an optimization algorithm that generates building configurations. This method requires a geographic model that supports the formalization of the Right to Build regulation in order to check if a building respects it. The proposed approach relies on the trans-dimensional simulated annealing optimization method, which produces building configurations composed of a set of parametric objects (boxes in our implementation). Our proposition is released as the SimPLU3D Open-Source project (http://ignf.github.io/simplu3D/ ). In this paper, we present some tests and results based on this implementation and a use related to the assistance to 'Right to Build' designers. Graphical Abstract: Highlights: An Open-Source simulator is proposed to generate 3D buildings from Right to Build regulation Generic and extensible 3D regulation model that represents the urban environment and OCL for the regulation formalization The generation process is based on a trans-dimensional simulated annealing optimization algorithm It automatically determines the complexity of the generated building configurations The approach may be used for assistance in regulation parameterization or for the simulation of urban fabric evolution